Bahasa Inggris - Abdillah, Muhammad Nur; Nugrahani, Ilma; Fidriany, Irda; Humairoh, Rosnaini (Faculty of Mathematic and Natural Science, Garut University, 2025)
Honey with a bitter flavour available on the market is expected to meet quality standards outlined by the Indonesian National Standard (SNI). This study aimed to determine adulteration in such honey products using SNI as the benchmark. Tests conducted included analyzing moisture content through Karl Fischer titration, diastase activity, hydroxymethylfurfural (HMF) levels, sucrose concentrations via the Anthrone method by UV-visible spectrophotometry, and reducing sugar content using HPLC-RI. Eight honey samples were assessed—seven bitter and one sweet (as a reference). Findings revealed several bitter honey samples failed to comply with SNI criteria, signalling possible adulteration. These results underscore the importance of adhering to SNI to ensure honey quality.